A world revision of the bee fly tribe Usiini (Diptera, Bombyliidae) —Part 1: Usia subgenus Micrusia, U. versicolor (Fabricius) (= black-haired species) and Usia martini François - Gibbs, David (Zootaxa, 2011)
This first part of a world revision of the Usia Latreille and Parageron Paramonov, tribe Usiini Becker, covers the aberrant species Usia martini François, which is placed in its own species group, and all of the black-haired species. The subgenus Micrusia Evenhuis is redefined and Usia versicolor (Fabricius) and Usia martini François are placed in their own species groups. The 20 species in Micrusia are considered to be monophyletic despite many of them exhibiting strong divergence that obscures their affiliations. Of the 10 formerly available names that belong in the subgenus Micrusia, U. hyalipennis Macquart stat. rev., hitherto synonymised under U. versicolor, is reinstated as a full species while U. pallescens Becker syn. nov., is newly synonymised under U. ignorata Becker. Both sexes of all previously named species are redescribed, for U. carmelitensis Becker, U. hyalipennis, U. martini and U. syriaca Paramonov the male is described for the first time. Twelve new species are described, U. biconvexa sp. nov., U. crispa sp. nov., U. cryptocrispa sp. nov., U. dahli sp. nov., U. dilsi sp. nov., U. echinus sp. nov., U. falcata sp. nov., U. globicauda sp. nov., U. paracrispa sp. nov., U. susanae sp. nov., U. theodori sp. nov. and U. turaco sp. nov. more than doubling the total in Micrusia. Both the male and female genitalia of all 22 species treated in this part are illustrated in detail.